Influence of Geography on the Formation of Ancient Civilizations: An Analysis of the Role of the Natural Environment in the Development of Early Societies - Fayaz Gul Mazloum Yar; Mastali Niazai (Jurnal Syntax Transformation, 2025)
This article examines the role of geography in the formation of ancient civilizations such as Egypt, Mesopotamia, the Indus Valley, and China. By analyzing environmental factors such as rivers, fertile soil, climate, and geographic location, we demonstrate how these factors acted as primary drivers in the development of agriculture, trade, and social organization. The research methodology of this article is based on historical-geographical analysis utilizing library resources, historical documents, and archaeological data. The findings indicate that rivers, as vital arteries, enabled sustainable agriculture and trade, while climate and fertile soil contributed to economic and population growth. Furthermore, strategic geographic locations acted as key factors in shaping political boundaries and cultural interactions. This article concludes that geography not only served as an environmental factor but also acted as a driving force in the evolution of human societies. Future research is suggested to focus on the impact of geography on lesser-known civilizations and the role of technology in overcoming geographical limitations.